HTLV-1 p13 Protein Hijacks Macrophage Polarization and Promotes T-Cell Recruitment - Ramona Moles; Maria Omsland; Cynthia A. Pise-Masison; Jeffrey J. Subleski; Daniel W. McVicar; Sarkis Sarkis; Anna Gutowska; Luca Schifanella; Melvin Doster; Robyn Washington-Parks; Vincenzo Ciminale; Genoveffa Franchini (Viruses)
The human T-cell leukemia type-1 (HTLV-1) retrovirus establishes chronic life-long infection in a fraction of infected individuals associated with severe pathological conditions. Although the mechanism driving disease development is not fully understood, current evidence indicates the essential functions of viral regulatory proteins. Among these, the p13 protein has previously been shown to localize to the inner mitochondrial membrane in T cells, altering mitochondrial biology and T-cell function. While CD4+ T cells are the primary cell target of HTLV-1 infection, genomic viral DNA has also been detected in monocytes, macrophages, and dendritic cells, which orchestrate innate and adaptive immunity and play a critical role in protecting against virus-induce diseases by establishing the appropriate balance of pro and anti-inflammatory responses. Given the central role of mitochondria in monocyte differentiation, we investigated the effect of p13 in monocytes/macrophages and found that by localizing to mitochondria, p13 affects mitochondrial respiration. Moreover, we demonstrate that p13 expression affects macrophage polarization to favor the recruitment of CD4+ T cells, the primary target of the virus, potentially facilitating the spread of viral infection and the development of disease.